The Effectiveness Of Using Flashcards To Improve Vocabulary In Speaking English For Elementary School Students - Rindika Pramadanti (Simpati, 2023)
This study set out to show how instructors may effectively use visual media. English classes are also chosen as a local subject in elementary schools (flashcards) to enhance the oral vocabulary of elementary school students. The planning, execution, observation, and reflection phases are included in each study cycle based on the classroom action research methodology. Researchers utilize test sheets and observations as instruments to retrieve data. The results showed that students' scores reached 75 in period I, then increased to 82 in period II. As illustrated in the observation table, student activity increased. The sample in this study was grade IV students of SD Zamzam Kurnia Bekasi. The results showed an improvement in English speaking skills. Therefore, using Flashcard media can increase students' vocabulary in improving students' English speaking skills in class.